Analisis Proses Kognitif Siswa dalam Menyelesaikan Soal Matematika Berdasarkan Taksonomi Bloom pada Materi Persegi dan Persegi Panjang SMP Kristen Weemaringi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze students' cognitive processes when solving mathematics problems regarding squares and rectangles, based on Bloom's Taxonomy, in the seventh-grade class at Weemaringi Christian Junior High School. A descriptive method was employed, involving the entire seventh-grade cohort of nine students. Data were collected through tests, interviews, and documentation, and subsequently analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the students' cognitive processes remain dominated by low- to mid-level thinking skills. Test results show that six students (67%) fell into the medium category and three students (33%) into the low category, with no students reaching the high category. At the C1 cognitive level, students were able to recall previously learned concepts, formulas, and information. However, at levels C2, C3, and C4, some students still struggled to understand concepts, apply formulas, and analyze problems. At levels C5 and C6, students were not yet able to evaluate solution steps or independently create problems and their solutions. The study concludes that the students' cognitive processes have not yet optimally achieved high-level thinking skills. Teachers are advised to provide practice problems that focus on the skills of analyzing, evaluating, and creating